Inhibition of Urokinase-Type Plasminogen Activator Expression by Macelignan in Porphyromonas gingivalis Supernatant-Induced Human Oral Epithelial Cells - . Yanti (HAYATI Journal of Biosciences, 2010)
This study was to investigate the effect of macelignan on Porphyromonas gingivalis supernatant-induced uPA expression via regulating mitogen-activated protein kinase (MAPK) and activating protein-1 (AP-1) signaling pathways in human oral epithelial KB cells using casein zymography, Western blotting, reverse transcription-PCR and reporter gene assays. Zymographic analysis of secreted enzymes identified the main caseinolytic band at 54 kDa. Macelignan inhibited the expression of uPA protein and mRNA, as well uPA secretion, in KB cells exposed to P. gingivalis supernatant. Consistent with these findings, macelignan suppressed phosphorylation of p38 and c-Jun N terminal kinase (JNK) in P. gingivalis supernatant-induced KB cells. The levels of c-Fos and phosphorylated c-Jun, which together form AP-1, the transcription factor that is involved in uPA gene expression, were partially reduced by macelignan. Macelignan also blocked P. gingivalis supernatant-induced AP-1 activity in these cells. These results suggest that macelignan decreased P. gingivalis supernatant-induced uPA expression by blocking AP-1 activity, which may be mediated by inhibition of phosphorylation of p38 and JNK in KB cells. Macelignan may potently use for the modulation of periodontal inflammation.